(untitled) (Asian Journal of Medical and Biological Research, 2016)
Aspergillus flavus strains were isolated from locally available poultry feeds. Effect of temperature, pH and culture media on growth of Aspergillus flavus was studied. Temperature ranged from 4-42°C (4, 10, 20, 25, 30, 37 and 42°C) was examined. Except for 4°C and 10°C, the isolate was able to grow for the whole temperature range. The growth was maximum at 25°C and was influenced with increasing or decreasing of temperature from 42°C to 20°C.The lag time was strongly influenced by the temperature at lower temperature level than at higher temperature range. Effect of pH on growth of Aspergillus flavus was also examined; from comparison of 3 different pH levels, it is concluded that at most temperatures pH 6.5 showed a higher growth rate and as a consequence required a shorter time to achieve maximum colony diameter. No significant variations in the lag time were observed. A natural poultry feed meal agar medium (FMAM) was developed in the laboratory and growth of A. flavus was compared with other 2 synthetic dehydrated media namely; Czapeksdox Agar (CDA) and potato dextrose Agar (PDA). Poultry feed meal agar medium showed better growth response than Czapeksdox agar and potato dextrose agar at all conditions. At 25°C and pH 6.5 found optimum for growth of Aspergillus flavus in feed meal agar medium whereas, temperature 30°C and pH 6.5 found optimum for growth for Czapeksdox agar media and temperature 30°C and pH 6 showed high growth rate on potato dextrose agar. Poultry feed meal media showed high affinity for growth of mycelium and early spore formation than other media examined. Asian J. Med. Biol. Res. June 2016, 2(2): 221-228